Context and agency in urban community energy initiatives: An analysis of six case studies from the Baltic Sea Region. (January 2021) - Ruggiero, S.; Busch, H.; Hansen, T.; Isakovic, A.
Abstract: In this paper, we analyse community energy (CE) projects in urban settings. Building on insights from the literature on the geography of sustainability transitions, we examine how contextual conditions promote or hinder the development of CE. Furthermore, reflecting on calls for greater attention to agency in transitions, we investigated how actors engaged in urban CE projects exploit beneficial conditions or overcome obstacles related to some of the contextual conditions. Empirically, we draw on six case studies of CE projects from the Baltic Sea Region. To develop a thorough understanding of our cases we conducted 24 semi-structured interviews and analysed numerous secondary sources. Our results show that institutions as well as visions, e.g. plans for future energy generation, are important contextual features for urban CE projects. Local actors seek to overcome unfavourable contextual conditions for CE initiatives by building trust, appealing to their community's sense of identity, networking, and promoting demonstration projects. Based on the results, we recommend that local and national governments address the following four issues to strengthen the role of CE in the transformation of urban energy systems: 1) harmonising policies; 2) creating a culture for transitions; 3) developing visions for CE; and 4) promoting policy learning from experiments. Highlights: The paper examines urban community energy (CE) projects in the Baltic Sea region. It establishes a framework for analysing the influence of contextual factors on CE. Institutions and visions are particularly important for CE development. Strategies for overcoming unfavourable contextual conditions are identified. Policy should not only support CE but also stimulate cultural change in some contexts.